MODAL SOSIAL DALAM URBAN TOURISM DI JOHO KAMPOENG HEPI KOTA SURAKARTA - Salsa Bila, Linda; Puspo Priyadi, Budi; Hayu Dwimawanti, Ida (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
This study discusses social capital in Urban Tourism in Joho Kampoeng HEPI Surakarta City. Urban Tourism is a tourist resource located in urban areas with main elements and supporting elements to attract tourists. One form of Urban Tourism in Indonesia is the emergence of thematic villages. One of them is Joho Kampoeng HEPI in Surakarta City which has its own uniqueness so that it has the potential to become an Urban Tourism area. However, Joho Kampoeng HEPI after being designated as a thematic village was unable to grow and develop sustainably. The development of tourism can be seen through the form of social capital owned by each actor involved. The purpose of this study is to find out how social capital is formed in Joho Kampoeng HEPI and find out the reasons why Joho Kampoeng HEPI cannot grow sustainably. This research method uses qualitative methods with descriptive data analysis with the selection of research subjects using the Purposive Sampling method. Data collection techniques through interviews, observation, documentation, and literature studies with primary and secondary data sources. Data analysis is carried out through three stages, namely data condensation, data presentation, and conclusions. The validity test or validity of the data in this study was carried out by the triangulation method. Researchers analyzed the research using social capital theory which includes three aspects, namely bonding social capital, bridging social capital, and linking social capital. Tourism problems that arise in Joho Kampoeng HEPI are also analyzed using several aspects in Urban Tourism, namely attractions, accessibility, amenities and accommodations, and institutions. The results of the study show that the existing social capital does not guarantee the development of Urban Tourism in Joho Kampoeng HEPI to grow sustainably if it is not supported by the elements of Urban Tourism as a whole. The recommendations given include increasing commitment to collaboration and coordination, capacity and resource development, increasing innovation in the management of tourist attractions, strengthening social capital, and developing sustainable tourism strategies.